Microbially Mediated Ore-Forming Processes and Cell Mineralization - Polgári, Márta; Gyollai, Ildikó; Fintor, Krisztián; Horváth, Henrietta; Pál-Molnár, Elemér; Biondi, João Carlos (Frontiers in Microbiology, 2019)
Sedimentary black shale-hosted manganese carbonate and oxide ores were studied by high resolution in situ detailed optical and cathodoluminescence microscopy, Raman and FTIR spectroscopy to determine microbial contribution in metallogenesis. This study of the Urucum Mn deposit in Brazil is inlcuded as a case study for microbially mediated ore forming processes. The results were compared and interpreted in a comparative way and the data were elaborated by a complex, structural hierarchical method. The first syngenetic products of microbial enzymatic oxidation were ferrihydrite and lepidocrocite on the Fe side, and vernadite, todorokite, birnessite, and manganite on the Mn side, formed under obligatory oxic (Mn) and suboxic (Fe) conditions and close to neutral pH. Fe- and Mn-oxidizing bacteria played a basic role in metallogenesis based on microtextural features, bioindicator minerals and embedded variable organic matter. Trace element content is determined by source of elements and microbial activity. The present Urucum (Brazil), Datangpo (China) and Úrkút (Hungary) deposits are the result of complex diagenetic processes, which include the decomposition and mineralization of cell and extracellular polymeric substance of Fe and Mn bacteria and cyanobacteria. Heterotrophic cell colonies activated randomly in the microbialite sediment after burial in suboxic neutral/alkaline conditions, forming Mn carbonates and variable cation-bearing oxides side by side with lithification and stabilization of minerals. Deposits of variable geological ages and geographical occurrences show strong similarities and indicate two-step microbial metallogenesis; a primary chemolithoautotrophic, and a diagenetic heterotrophic microbial cycle, influenced strongly by mineralization of cells and extracellular polymeric substances. These processes perform a basic role in controlling major and trace element distribution in sedimentary environments on a global level, and place biogeochemical constraints on the element content of natural waters, precipitation of minerals and also on water contaminants.